2022
DOI: 10.3389/fphar.2022.883629
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Rosa Roxburghii Tratt Juice Alleviates High-Fat Diet-Induced Hyperlipidemia in Rats by Modulating Gut Microbiota and Metabolites

Abstract: Hyperlipidemia endangers human health and has become a significant public health problem. This study aimed to investigate the mechanism of the hypolipidemic effects of Fermented Rosa roxburghii Tratt juice (FRRT) on hyperlipidemic rats and a new hypolipidemic intervention strategy was disclosed. The study revealed 12 weeks FRRT treatment significantly decreased the body weight, total cholesterol (TC), triacylglycerol (TG), low-density lipoprotein cholesterol (LDL-c), while high-density lipoprotein cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Similar situations also occurred in Allobaculum; in the present study, a positive correlation was found between the abundance of Allobaculum and metabolic parameters, while in some animal and human studies, Allobaculum was approved negatively with insulin resistance, inflammation, dyslipidemia, and obesity . Furthermore, bacteria like Oscillospira and Prevotella , which showed increased abundance in the HVA and HRA groups, have been associated with beneficial effects on lipid metabolism and liver damage, including the reduction of TC, TG, LDL-C, ALT, and AST levels, as well as the increase of HDL-C levels, which is consistent with our results. , These findings indicated that the changes observed in the abundance of specific bacterial taxa in our study could potentially contribute to the beneficial effects of VA and RA supplementation on obesity, liver damage, glucose tolerance, insulin resistance, lipid profile, and inflammation in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar situations also occurred in Allobaculum; in the present study, a positive correlation was found between the abundance of Allobaculum and metabolic parameters, while in some animal and human studies, Allobaculum was approved negatively with insulin resistance, inflammation, dyslipidemia, and obesity . Furthermore, bacteria like Oscillospira and Prevotella , which showed increased abundance in the HVA and HRA groups, have been associated with beneficial effects on lipid metabolism and liver damage, including the reduction of TC, TG, LDL-C, ALT, and AST levels, as well as the increase of HDL-C levels, which is consistent with our results. , These findings indicated that the changes observed in the abundance of specific bacterial taxa in our study could potentially contribute to the beneficial effects of VA and RA supplementation on obesity, liver damage, glucose tolerance, insulin resistance, lipid profile, and inflammation in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 79%
“…72 Furthermore, bacteria like Oscillospira and Prevotella, which showed increased abundance in the HVA and HRA groups, have been associated with beneficial effects on lipid metabolism and liver damage, including the reduction of TC, TG, LDL-C, ALT, and AST levels, as well as the increase of HDL-C levels, which is consistent with our results. 73,74 These findings indicated that the changes observed in the abundance of specific bacterial taxa in our study could potentially contribute to the beneficial effects of VA and RA supplementation on obesity, liver damage, glucose tolerance, insulin resistance, lipid profile, and inflammation in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 56%
“…Phytochemical analyses confirmed that RRT contains organic acids, flavonoids, polyphenols and other natural active ingredients, with functional activities incomparable to other fruits ( Wang et al, 2021 ). RRT exhibits a diversity of biological characteristics against immune disorder, inflammatory disease and tumors, and can also regulate gut microbiota dysfunction caused by hyperlipidemia and diabetes ( Wang et al, 2020 ; Ji et al, 2022 ). RRT polyphenol (RRTP), including phenolic acids, coumarins, lignans, tannins, and flavonoids, is one of the most important active components of RRT.…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids have even been suggested as treatment options for liver illness and obesity [19]. In addition, bile acids interact with gut microbes, which have been reported to be tightly connected to hyperlipidemia, and may be a new target for the therapeutic treatment of hyperlipidemia [20,21]. Wu et al indicated that gut microbes are essential for berberine to ameliorate hyperlipidemia [22].…”
Section: Introductionmentioning
confidence: 99%